The search for science and technology verses in Qur’an and hadith - Ichsan Taufik; Mohamad Jaenudin; Fatimah Ulwiyatul Badriyah; Beki Subaeki; Opik Taupik Kurahman (Bulletin of Electrical Engineering and Informatics, 2021)
Currently, the Vector Space Model algorithm has been widely implemented for the document search feature because of its reliability in retrieving information. One of them in the search for verses of the Qur'an based on the translation. However, if the phrase or word used is different (even though it has one meaning) with the word in the document in the database, the system will not display the verse. As we know that the Qur'an has a very deep meaning, so an interpretation of the verse is needed. Therefore, this research focuses on implementing the Vector Space Model (VSM) algorithm for searching verses and hadiths in science and technology by using the discussion parameters of these verses or hadiths. The test results obtained with 20 keyword samples using metric recall were 81% with an average time of 2.24 seconds.